Efektivitas Program Pemberian Makanan Tambahan (PMT) terhadap Partisipasi Masyarakat di Desa Maddenra Kacamatan Kulo Kabupaten Sidenreng Rappang - Aulia Rahman; Andi Uceng; Lukman Lukman (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to determine the effectiveness of the Supplementary Feeding Program (PMT) on community participation in Maddenra Village, Kulo District, Sidenreng Rappang Regency. Nutritional problems such as stunting and chronic energy deficiency are still challenges, and PMT is one of the government's interventions in overcoming them. The research method used is a quantitative approach with descriptive analytical techniques. The sample consisted of 30 respondents consisting of pregnant women and toddlers. Data were collected through observation, questionnaires, and literature studies. The results of the study showed that Supplementary Feeding (PMT) in Maddenra Village was considered "quite effective" with an average percentage of effectiveness of 76%. Community participation in the aspects of planning, implementation, and evaluation was also classified as "good" with an average percentage of 71%. Factors such as education, quality of supplementary food, infrastructure, and local policy support also influenced the success of the program with a percentage value of 70%. This study provides strengthening of nutritional education and increasing community involvement as a strategy to increase the effectiveness of the Supplementary Feeding (PMT) program in the future.